Developmental Flower and Rhizome Morphology in Nuphar (Nymphaeales): An Interplay of Chaos and Stability - El, Elena S.; Remizowa, Margarita V.; Sokoloff, Dmitry D. (Frontiers in Cell and Developmental Biology, 2020)
European species of Nuphar are among the most accessible members of the basal angiosperm grade, but detailed studies using scanning electron microscopy are lacking. We provide such data and discuss them in the evolutionary context. Dorsiventral monopodial rhizomes of Nuphar bear foliage leaves and non-axillary reproductive units (RUs) arranged in a Fibonacci spiral. The direction of the phyllotaxis spiral is established in seedlings apparently environmentally and maintained through all rhizome branching events. The RUs can be located on dorsal, ventral or lateral side of the rhizome. There is no seasonality in timing of their initiation. The RUs usually form pairs in positions N and N+2 along the ontogenetic spiral. New rhizomes appear on lateral sides of the mother rhizome. A lateral rhizome is subtended by a foliage leaf (N) and is accompanied by a RU in the position N+2. We hypothesize a two-step process of regulation of RU/branch initiation, with the second step possibly involving environmental factors such as gravitropism. Each RU has a short stalk, 1-2 scale-like phyllomes and a long-pedicellate flower. We support a theory that the flower is lateral to the RU axis. The five sepals initiate succesively and form two whorls as 3+2. The sepal arrangement is not ‘intermediate’ between whorled and spiral. Mechanisms of phyllotaxis establishment differ between flowers and lateral rhizomes. Petal, stamen and carpel numbers are not precisely fixed. Petals are smaller than sepals and form a whorl. They appear first in the sectors of the outer whorl sepals. The stamen arrangement is whorled to chaotic. The merism of the androecium tends to be the same as in the corolla. Flowers with odd numbers of stamen orthostichies are found. These are interpreted as having a non-integer merism of the androecium (e.g., 14.5). Carpels form a whorl in N. lutea and normally alternate with inner whorl stamens. Sterile second whorl carpel(s) are found in some flowers of N. pumila.